SIMILARITY AND QUASISIMILARITY OF BILATERAL OPERATOR VALUED WEIGHTED SHIFTS - Ivanovski, Novak (Matematichki Bilten, 1993)
In this paper we study the problem of quasisimilarity of bilateral operator valued weighted shifts which is a generalization of a result of Fialkow for the scalar valued weighted shifts.